Factors influencing the decision to use BSI Mobile Banking among Gen Z and Millennials in Yogyakarta, Indonesia - Fitriah , Yasminah Nur; Garbo, Anom (Universitas Islam Indonesia, 2024)
IntroductionMobile banking has become an essential aspect of modern financial services, particularly among digitally literate populations such as Gen Z and Millennials. Despite the widespread adoption of mobile banking, understanding the factors influencing its use in specific cultural and demographic contexts remains underexplored. This study investigates the adoption of Bank Syariah Indonesia's (BSI) mobile banking services among Gen Z and Millennials in Yogyakarta using the Unified Theory of Acceptance and Use of Technology 2 (UTAUT2) framework.ObjectivesThe research aims to identify and analyze the key factors driving the decision to adopt mobile banking services, focusing on intrinsic motivators such as performance expectancy, effort expectancy, hedonic motivation, price value, and habit, as well as external factors like social influence and facilitating conditions.MethodThis study employed a quantitative approach, collecting data from 124 respondents through structured questionnaires. Using Partial Least Squares Structural Equation Modeling (PLS-SEM), the relationships between the UTAUT2 factors and mobile banking adoption were evaluated.ResultsThe findings indicate that intrinsic factors, particularly habit, performance expectancy, and effort expectancy, significantly influence mobile banking adoption. Hedonic motivation and price value also play essential roles, whereas external factors such as social influence and facilitating conditions were found to have no significant impact.ImplicationsThe study underscores the importance of user-centered strategies that enhance functionality, ease of use, and emotional satisfaction. It suggests that financial institutions should focus on fostering habitual engagement and cost-effective services to drive adoption.Originality/NoveltyThis research contributes to the literature on digital financial services by offering insights into mobile banking adoption among Gen Z and Millennials in Indonesia, emphasizing the relevance of intrinsic motivators in a technologically advanced context.